Solomonseal Polysaccharide and Sulfated Codonopsis pilosula Polysaccharide Synergistically Resist Newcastle Disease Virus - Liu, Cui (PLoS One, 2015)
Five combinations of three ratios (PS(9)-sPS(1), PS(7)-sPS(3) and PS(6)-sPS(4)) were prepared with polysaccharide (PS) and sulfated polysaccharide (sPS). The antiviral activities of these compounds were subsequently compared in vitro using the MTT assay, observation of the virus structure and immunofluorescence. The results demonstrated that SP(9)-sCP(1), CP(7)-sCA(3), EP(7)-sAP(3), CA(9)-sEP(1) and EP(7)-sCA(3) presented higher activities, and SP(9)-sCP(1) displayed the highest virus inhibition rate and clearly killed the virus and inhibited viral antigen expression. In an in vivo test, 28-day-old chickens were challenged with Newcastle disease virus (NDV) and were administered the five drug combinations. On day 14 after the challenge, the morbidity, mortality and cure rate in each group were calculated. The results indicated that SP(9)-sCP(1) presented the lowest morbidity and mortality and the highest cure rate. These results indicate that Solomonseal polysaccharide and sulfated Codonopsis pilosula polysaccharide synergistically resist NDV. Moreover, SP(9)-sCP(1) had the highest efficacy and may be used as a new antiviral drug.